Exposure therapy vs lifestyle intervention to reduce food cue reactivity and binge eating in obesity: A pilot study. (June 2020) - Schyns, Ghislaine; van den Akker, Karolien; Roefs, Anne; Houben, Katrijn; Jansen, Anita
Abstract: Background and objectives: Learning models of overeating predict that exposure therapy is effective in reducing food cue reactivity and overeating. This pilot study tested an eight-session exposure therapy aimed at inhibitory learning vs. an active control condition aimed at lifestyle improvement for obesity (treatment-as-usual). Main outcomes are snacking behavior, eating psychopathology, food cue reactivity, and weight loss. Change in overeating expectancies was assessed as mediator for outcomes, and the associations between habituation of eating desires and outcomes were investigated in the exposure condition. Sleep quality was investigated as moderator for outcomes. Methods: 45 overweight women were randomly assigned to the exposure intervention or control condition. The main outcomes, overeating expectancies and sleep quality were re-assessed at post-treatment and three-month follow-up. Habituation of eating desires was measured during exposure sessions. Results: Compared to the control intervention, exposure led to a significantly stronger reduction in snacking behavior of exposed foods, though this effect did not generalize to non-exposed foods, and stronger binge eating frequency. The exposure condition lost significantly more weight at post-treatment and follow-up than the lifestyle condition. Changes of expectancies mediated the effect of condition on kcal consumption of exposed foods, while habituation during exposure was not related to better treatment outcome. Sleep quality did not moderate the effect of condition on treatment outcome. Limitations: Small sample size and limited follow-up period. Conclusions: This short exposure therapy reduced snacking behavior, binge eating and weight more than a lifestyle intervention and is therefore a recommendable intervention for obesity and overeating disorders. Highlights: We tested 8 sessions cue exposure therapy vs. control intervention in obese females. Cue exposure led to stronger reductions in binge eating and body weight. Cue exposure led to less kcal intake of personal exposed foods. Habituation of eating desires was not related to better treatment outcome. Stronger change in overeating expectancies was related to better treatment outcome.